Venous ulcer: characterization of outpatient care at a university hospital (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To characterize the clinical and sociodemographic profile of people with venous ulcers followed up in a specialize outpatient clinic of a university hospital. Method: documentary study carried out in a general surgery outpatient clinic of a university hospital. 104 instruments applied in the first nursing consultation were reviewed. Results: there was a predominance of females, with a mean age of 54 years. The majority did not perform paid work, the wound being the reason for leaving work activities. Systemic arterial hypertension and obesity were the most prevalent comorbidities. The person with venous ulcer was the main person involved in direct care of the wound. Conclusion: the profile of the study population is compatible with other studies in different contexts in Brazil. The results allow a reflection on the assistance provided and the effectiveness of the implemented interventions.